Disclosure of Medical Errors: Attitudes of Iranian Internists and Surgeons - Tagaddosinejad, F; Mesri, M; Sheikhazadi, A; Mostafazadeh, B; Farahani, M (International Journal of Medical Toxicology and Forensic Medicine, 2013)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> <![endif]–> Background: Despite the widespread prevalence of medical errors and increased concerns of healthcare managers and the public about the disclosure of medical errors in recent decades, existing evidence shows that physicians still ignore the importance of disclosure of those errors. The present study aims to investigate the attitudes of Iranian internists and surgeons towards the disclosure of medical errors. Method: In this cross-sectional study, after a research purpose briefing, a checklist eliciting basic information and a questionnaire measuring attitudes towards the disclosure of medical errors was distributed to participant physicians at Imam Khomeini Hospital, Tehran, Iran. The questionnaires were returned filled out by 107 participants (54 internists and 53 surgeons). Results: Although 77%, 53% and 44% of the participants agreed to the disclosure of serious, minor and near miss medical errors, respectively, 83% believed that it’s very difficult for them to disclose medical errors and 48% asserted that disclosure of medical errors would threaten patients’ trust in physicians. In addition, 78% of the participants believed in notifying hospital or ward authorities of the occurrence of medical errors while only 53% agreed to notify colleagues in case of medical errors. Patients’ litigations (51%), unfamiliarity with patients’ temperament (46%) and patients’ asperity (40%) were the most prevalence reasons for nondisclosure of medical errors. No significant difference was found among participants’ attitudes in terms of sex and age groups (p>0.05). In terms of specialty, surgeons expressed significantly more agreement than internists about declaration of medical errors to hospital and ward authorities (87% Vs 70%, p=0.039) and to other colleagues (66% Vs 41%, p=0.009). In addition, the surgeons believed that the disclosure of medical errors would minimize the likelihood of patients’ litigations (60% Vs 42%, p=0.049). Internists and surgeons’ attitudes did not differ over other issues (p>0.05). Conclusion: Although the majority of specialists agreed to the disclosure of serious medical errors, more than 80% of them regarded it as an awkward act. In addition, half of the participants considered disclosure as a threat to patient trust and felt deterred by patients’ litigations. Therefore, it seems that disclosure of medical errors is a serious issue in Iran which needs to be addressed by healthcare system policy makers.